Modelado y Análisis de técnicas de acceso basadas en geolocalización para V2V - Alarcón, Daniel; Gómez, Gerardo; Martín-Vega, Francisco-Javier (My University, 2021)
In this work, two geolocation-based access (GLOC) techniques for vehicular communications are presented and analyzed. These techniques, named Single-Lane Partition (SLP) and Multiple-Lane Partition (MLP) differ on the allocation of transmission resources between different lanes of the road. To assess the benefits of both approaches it is devised a realistic system model that considers the random nature of vehicle locations by means of a Poisson Point Process (PPP), the propagation losses, fast fading, and inter-vehicle interference. Two main types of messages in vehicular communications are considered: Cooperative Awareness Messages (CAM) and Decentralized Environmental Notification Messages (DENM). Simulation results lead to important insight about the behavior of the considered techniques in terms of the Signal to Interference-plus-Noise Ratio (SINR) distribution, i.e., capture probability, the binary rate and the energy efficiency. Results show that MLP performs better at the expense of a greater waste of resources.
Keywords: Sistema de transporte inteligente; geo-localización; comunicaciones vehiculares; planificación de recursos; gestión de interferencias